Scale up of a Plasmodium falciparum elimination program and surveillance system in Kayin State, Myanmar [version 1; referees: 2 approved] - Daniel M. Parker; Jordi Landier; Aung Myint Thu; Khin Maung Lwin; Gilles Delmas; François H. Nosten; The Malaria Elimination Task Force Group (Wellcome Open Research, 2017)
Background: Myanmar has one of the largest malaria burdens in Southeast Asia. Along the border with Thailand, Plasmodium falciparum parasites are increasingly showing reduced sensitivity to artemisinin combination therapies. Given that there are no current alternative treatment therapies, one proposed solution to the threat of untreatable P. falciparum malaria is to eliminate the parasite from the region. Several small-scale elimination projects have been piloted along the Myanmar-Thailand border. Following their success, this operational research aimed to scale up the elimination to a broad area of Eastern Kayin State, Myanmar. Methods: The project relied on geographic reconnaissance and a geographic information system, community engagement, generalized access to community-based early diagnosis and treatment, near real-time epidemiological surveillance, cross sectional malaria prevalence surveys and targeted mass drug administration in villages with high prevalence of P. falciparum malaria. Molecular markers of drug resistance were also monitored in individuals with symptomatic and asymptomatic infections. Discussion: This project illustrates the establishment of an elimination project and operational research in a remote, rural area encompassing several armed groups, multiple political organizations and a near-absent health care infrastructure. The establishment of the project relied on a strong rapport with the target community, on-the-ground knowledge (through geographic surveys and community engagement), rapid decision making and an approach that was flexible enough to quickly adapt to a complex landscape. The elimination project is ongoing, now over three years in operation, and assessment of the impact of this operational research will follow. This project has relevance not only for other malaria elimination projects but also for operational research aimed at eliminating other diseases.